Haemosporidian parasites of barred owls (Strix varia) and northern spotted owls (S. occidentalis caurina): investigating the effects of an invasive species on parasite transmission and community dynamics - Lewicki, Krista E., author; Huyvaert, Kathryn P., advisor; Franklin, Alan B., advisor; Piaggio, Antoinette J., committee member; Pejchar Goldstein, Liba, committee member; Foy, Brian D., committee member (Colorado State University. Libraries, 2013)
Although the barred owl (Strix varia) was historically limited to eastern sections of North America, its range has steadily expanded westward over the past century. Currently the barred owl's range entirely overlaps the range of the federally threatened northern spotted owl (Strix occidentalis caurina) in the Pacific Northwest. Invasive species have been known to drastically impact a region's native species by altering the parasite communities among those species, yet little is known about the parasites of barred and northern spotted owls in particular. The purpose of this study was to determine if and to what extent avian blood parasite assemblages of barred and northern spotted owls have changed as a result of the range expansion by barred owls. Blood samples were collected from sympatric northern spotted and barred owls in northwestern California, as well as from barred owls from seven regions across the barred owl's historic range. I screened samples for blood parasites belonging to the genera Haemoproteus, Plasmodium, and Leucocytozoon, and I analyzed bird infection status and intensity using a combination of PCR and microscopy techniques. Additionally, a section of mitochondrial DNA was sequenced from all samples in which I detected Haemoproteus or Plasmodium parasites, and I used these sequence data to calculate parasite haplotype richness, haplotype diversity, and similarity of Haemoproteus and Plasmodium assemblages. Using these five metrics I evaluated predictions of four hypotheses describing how biological invasions might affect parasite assemblages of invasive and native hosts: the Enemy Release (i.e., hosts benefit from a loss of parasites in their invasive range), Enemy of My Enemy (i.e., invasive hosts introduce parasites to naïve native hosts), Parasite Spillback (i.e., invasive hosts act as a new reservoir to native parasites), and Increased Susceptibility (i.e., native hosts introduce parasites to naïve invasive hosts) Hypotheses. Analyses of Leucocytozoon spp. indicated that the population from which the samples were collected (i.e., eastern barred or western barred) was not important in determining a barred owl's infection status, which offered little support for the Enemy Release Hypothesis (ERH) in the context of Leucocytozoon parasites. However, population was an important explanatory variable in determining a barred owl's infection status, parasite richness, and parasite diversity in analyses of Haemoproteus haplotypes, offering strong support for the ERH in the context of this genus of parasite. These findings suggest that barred owls may be released from the costs associated with some, but not all, parasite infections in the Pacific Northwest. Additional analyses of Haemoproteus haplotypes allowed me to detect a phylogeographic pattern in which one haplotype was common in both barred and northern spotted owls throughout North America, three haplotypes appeared to be isolated to the barred owl's historic range, while a fifth haplotype was notably divergent from all of the other detected haplotypes and seemingly isolated to California owls. Furthermore, probability of infection analyses indicated that host population (i.e., western barred or northern spotted) was an important explanatory variable in determining parasite diversity and a bird's infection status. These findings offer some support for the Parasite Spillback Hypothesis, suggesting that barred owls may be contributing to higher parasite prevalence among northern spotted owls by serving as an added reservoir host to northern spotted owl populations. Plasmodium spp. infections were rare among both barred and northern spotted owls, and I found no evidence that the barred owl range expansion has yet impacted the occurrence of Plasmodium spp. within northern spotted owls. Overall, this study demonstrates the complexity of host-parasite relationships and suggests that differences in parasite ecology across genera play an important role in determining whether or not parasites will persevere and be transmitted across invasive and native host populations. In addition, this study has identified a number of blood parasite haplotypes infecting barred and northern spotted owls, yet many questions still remain regarding the true cost of these parasite infections among barred and northern spotted owls and the implications of these infections for northern spotted owl conservation and management.